A Hieroglyphic Reading of the Modern Tehran Metropolis through Mindscape Constructing Factors, the Case of Tehran Shuttle Taxi Drivers - Nazila Rashid Pour; Manouchehr Tabibian; Seyed Mohsen Habibi (صفه)
The metropolis, modernity, and the capitalist economy are inseparable, and it is not possible to investigate each one in isolation. Dominated by of modernity, power and hegemony of capitalism, the metropolis has turned into an encoded space of content and meaning, with its own mysterious language, continuous influences the residents’ self-awareness. It produces a metropolitan typology in accordance with the existing urgency and complexity, and generated increasingly alienated people. It has caused a discontinuous and disintegrated experience of time and space that disrupts processes of forming image and memory of the city. From the left’s point of view, knowing the reality of cities depends on deciphering these meaningful images that require cognitive methods beyond positivist methods. To understand the metropolis is – to some extent – to understand our present age. Wherever the hieroglyphics of any spatial image are deciphered, there the basis of social reality presents itself. What we see on the surface, so any Marxist-inspired cultural theorist would argue, is the product of deeper underlying forces, and in order to understand these forces we need to interpret the surface level. From this point of view, reading what has never been written by re-reading the experience and understanding the image of the city can be useful in showing the neglected realities caused by the metropolis, modernity and capitalist economy. Assuming the city as a text for explaining the hieroglyphs of the modern metropolis of Tehran in representing the mysterious language of the city, quantitative and qualitative content analysis method was used in this research. For a concrete study of informal story and understanding the received messages through taxi drivers’ mindscape, and image readout was carried out. Analysing the informal stories shows that there is not any integrated policy for a purposeful representation of Tehran or there is no right tool for this purpose. According to the findings, we can claim that the language of the modern Tehran metropolis under the effect of Modernity paradigm and Capitalism is so discontinuous and disintegrated that it deteriorates any formation of memory.